2013
DOI: 10.1364/ol.38.000362
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared luminescence in TlCl:Bi crystal

Abstract: Experimental and theoretical studies of spectral properties of crystalline TlCl:Bi are performed. Two broad near-infrared luminescence bands with a lifetime of about 0.25 ms are observed: a strong band near 1.18 μm excited by 0.40, 0.45, 0.70, and 0.80 μm radiation and a weak band at ≳1.5 μm excited by 0.40 and 0.45 μm radiation. Computer modeling of Bi-related centers in TlCl lattice suggests that a Bi(+)…VCl(Cl)(-) center (Bi(+) in Tl site and a negatively charged Cl vacancy in the nearest anion site) is mos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
31
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 16 publications
0
31
0
1
Order By: Relevance
“…But, the near-infrared (NIR) emission band of REdoped films is narrow, severely limiting further development of optical communication. Fortunately, Bi-doped materials with broadband NIR luminescence covering the whole optical communication region are emerging [5][6][7][8]. Recently, various types of Bi-doped fiber lasers and amplifiers have been demonstrated in 1150~1550 nm region [9].…”
Section: Introductionmentioning
confidence: 99%
“…But, the near-infrared (NIR) emission band of REdoped films is narrow, severely limiting further development of optical communication. Fortunately, Bi-doped materials with broadband NIR luminescence covering the whole optical communication region are emerging [5][6][7][8]. Recently, various types of Bi-doped fiber lasers and amplifiers have been demonstrated in 1150~1550 nm region [9].…”
Section: Introductionmentioning
confidence: 99%
“…Calculation results have shown that the influence of the AgCl lattice on other Bi-related centers under study is substantially reduced to the crystal field effect and in a qualitative sense is described by the model similar to that suggested in [11] and used in [5,6]. However, we should emphasize that although this model allows visual interpretation of the origin of states in Bi-related centers, it describes the occurring electronic structure only roughly.…”
mentioning
confidence: 89%
“…Later IR luminescence was observed in TlCl:Bi crystals (Pm3m lattice) [5]. Probable IR luminescence centers in CsI and TlCl were studied then by a computer simulation technique [5,6].This Letter is devoted to the study of IR luminescence in AgCl:Bi crystals with a face-centered Fm3m lattice.The crystal was grown from silver chloride salts deposited from aqueous AgNO 3 solution after drying and purification by the method of directional (oriented) melt crystallization. Before growth 30 g of AgCl ligature with metal Bi or bismuth chloride (BiCl 3 ) dopant (0.076 mass.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery of the broadband near-infrared (NIR) photoluminescence from bismuth doped glasses [1][2][3][4][5] and crystalline materials [6][7][8][9][10][11][12][13][14][15][16][17][18][19] the nature of corresponding luminescent species is widely discussed. The Bi 3+ ion in the common oxidation state +3 has no optical transitions in NIR and the observed emission was attributed to possible Bi 5+ , 1 Bi 2+ , 20 Bi + , 21 Bi 0 , 8,9,22 Bi 2 À , Bi 2 2À , 23 and bismuth cluster species.…”
Section: Introductionmentioning
confidence: 99%